Scolopendromorpha of New Guinea and adjacent islands (Myriapoda, Chilopoda) - Schileyko, Arkady A.; Stoev, Pavel E. (Zootaxa, 2016)
The centipede fauna of the second largest island in the world, New Guinea, and its adjacent islands, is poorly known, with most information deriving from the first half of the 20th century. Here we present new data on the order Scolopendromorpha based on material collected in the area in the last 40 years, mainly by Bulgarian and Latvian zoologists. The collections comprise eleven species of six genera and three families. The diagnosis of Cryptops (Trigonocryptops) is emended in the light of the recent findings. The old and doubtful record of Scolopendra multidens Newport, 1844 from New Guinea is referred to S. subspinipes Leach, 1815 and the species is here excluded from the present day list of New Guinean scolopendromorphs. Cryptops nepalensis Lewis, 1999 is here recorded from New Guinea for the first time. An annotated list and an identification key to the scolopendromorphs of the studied region are presented.